Análisis del servicio de consejería estudiantil en la facultad de Ciencias de la Educación y Humanidades de la Universidad Nacional de la Amazonía Peruana 2022 - Tapullima Silis, Rosa (2024)
In this research study, the general objective was to compare the quality of student counseling services at the Faculty of Education and Humanities Sciences of the National University of the Peruvian Amazon 2022, according to professional careers. The research was of comparative type with field, contemporary cross sectional, and univariate designs. Data collection was carried out using a valid and reliable questionnaire. Among the main findings were that the student counseling service in its planning and execution stages fell within the categories of average, while it was deficient in the evaluation stage. It is concluded that there are no statistically significant differences in the counseling service among the ten professional careers in their planning and execution dimensions (p< α=0.05), however there are differences in the evaluation stage (p< α=0,05).